Seed-Borne Fungi Associated with Foxtail Millet (Setaria italica L. Beauv.) Genotype ICERI-6 - Khairani, Hagia Sophia; Ardie, Sintho W. (Akta Agrosia, 2020)
The need of functional foods that provide health benefits beyond the essential nutrient has caused foxtail millet (Setaria italica L. Beauv.) potential to be developed. The foxtail millet superior development needs to be equipped by the production of pathogen-free seeds. Seed-borne pathogens have the potential to inhibit plant growth, reduce plant productivity, change the nutritional content of plants, and may cause new plant disease epidemics. This study aimed to detect and identify fungi associated with foxtail millet seeds genotype ICERI-6 from the Indonesian Cereal Research Institute, Maros which have 8 mo shelf life. Seeds surface-sterilized with NaOCl was grown on potato dextrose agar (PDA) and incubated for 4 days. Detected fungal colonies were recultured on PDA medium to be characterized by morphological characteristics. The colonies were dominated by Fusarium oxysporum (52%) followed by F. verticilloides, Curvularia sp., Helminthosporium sp., Cladosporioum sp., and Rhizoctonia solani ranging from 4% to 13%. The fungal growth rate varies from 0.73 - 2.67 cm per day. Hot water treatment with temperature 52 oC for 20 min could reduce the percentage of infection by up to 64% without the reduction of seed germination. Detection of pathogens at different shelf lives and genotypes is needed as basic information to optimizing the method of controlling seed-borne pathogen in foxtail millet seeds.  Keywords: growth rate, hot water treatment, incubation, morphological characterization, shelf life.